SEVEN ISSUES AND DILEMMAS IN LITERATURE TEACHING IN EFL CONTEXT: LESSONS FROM INDONESIA - Musthafa, Bachrudin (Universitas Pendidikan Indonesia, 2015)
Abstract: Using literature instruction practices in different â€œliterature programsâ€ as a point of departure, this article discusses some knotty issues and dilemmas confronting English literature instructors and researchers in Indonesia, especially those working in the context of English as A Foreign Language (EFL). First some commonly adopted approaches to literature teaching are outlined and specific issues and dilemmas located. Next, using Indonesian current situation as a case in point, these perceived issues and dilemmas are fleshed out and possible solutions from diverse fronts are then sketched out.